Catalytic Disproportionation of Indonesian Gum Rosin over Pd/C Catalyst: GC–MS Analysis and Reaction Mechanism - Hardhianti, Meiga Putri Wahyu (Eksergi, 2026)
Indonesian gum rosin is a renewable natural resource with a unique composition characterized by the presence of mercusic acid. This study investigates its catalytic disproportionation over a Pd/C catalyst in a sealed batch reactor at 200 °C and 240 °C to improve chemical stability and explore its reactivity. The reaction products were analyzed using FTIR and GC–MS after methylation. Abietic acid was identified as the most reactive resin acid, undergoing typical disproportionation into hydrogenated (e.g., dihydroabietic) and dehydrogenated (dehydroabietic) derivatives. The formation of dehydroabietic acid was favored at 200 °C, while higher temperature (240 °C) promoted hydrogenation and isomerization side reactions. In contrast, mercusic acid followed a distinct pathway, undergoing selective double-bond isomerization to form structural isomers without changes in molecular weight, as confirmed by identical molecular ions (m/z 364) in the mass spectra. These findings clarify the temperature-dependent reaction behavior of major resin acids and reveal the unique mechanistic role of mercusic acid in Indonesian gum rosin.